2004
DOI: 10.1890/02-4045
|View full text |Cite
|
Sign up to set email alerts
|

Late‐quaternary Vegetation Dynamics in North America: Scaling From Taxa to Biomes

Abstract: This paper integrates recent efforts to map the distribution of biomes for the late Quaternary with the detailed evidence that plant species have responded individualistically to climate change at millennial timescales. Using a fossil-pollen data set of over 700 sites, we review late-Quaternary vegetation history in northern and eastern North America across levels of ecological organization from individual taxa to biomes, and apply the insights gained from this review to critically examine the biome maps gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
520
1
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 496 publications
(550 citation statements)
references
References 126 publications
19
520
1
5
Order By: Relevance
“…For example, paleoecological evidence indicates that terrestrial plant, vertebrate, and insect communities rarely persist without compositional change for more than a few thousand years (23,48,56,57,64). Regional species pools undergo change as species migrate, abandoning newly unsuitable habitats and colonizing newly favorable territory (18,22,50). Climate exerts influence at all levels, both directly and indirectly via aggregation of influences from below and constraint by influences from above.…”
Section: Communities Come Communities Gomentioning
confidence: 99%
See 1 more Smart Citation
“…For example, paleoecological evidence indicates that terrestrial plant, vertebrate, and insect communities rarely persist without compositional change for more than a few thousand years (23,48,56,57,64). Regional species pools undergo change as species migrate, abandoning newly unsuitable habitats and colonizing newly favorable territory (18,22,50). Climate exerts influence at all levels, both directly and indirectly via aggregation of influences from below and constraint by influences from above.…”
Section: Communities Come Communities Gomentioning
confidence: 99%
“…Quaternary paleoecology focuses on ecological change at these intermediate timescales and in recent decades has emphasized climate change as the primary locus of explanation for ecological change (18)(19)(20)(21)(22)(23). Compared with community ecology, paleoecology is somewhat depauperate in theory and concept and is often deficient in spatial, temporal, and taxonomic precision.…”
mentioning
confidence: 99%
“…Much of the work done in the late Pleistocene of North America has shown that previous climatic regimes were characterized by communities that have no modern analogues (e.g. Overpeck et al 1992; Roy et al 1995;Graham et al 1996;Jackson et al 1997;Jackson & Overpeck 2000;Davis & Shaw 2001;Roy 2001;Williams et al 2001Williams et al , 2004Lyons 2003Lyons , 2005. Moreover, Williams et al (2001) demonstrated that non-analogue communities are found in regions of non-analogue climate.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many comparisons of glacial and postglacial communities have shown great dissimilarities-species have responded to environmental change individualistically, indicating that the structure and function of assemblages can change substantially over even short geological timescales (e.g., several thousand to a few million years) (1)(2)(3). Conversely, some researchers have argued for stability in community structure (4), leading to communities that may be composed of stable sets of ecological specialists for millions of years (5,6).…”
mentioning
confidence: 99%